Growth and shaping of metacarpal and carpal cartilage anlagen: application of morphometry to the development of short and long bone. A study of human hand anlagen in the fetal period. (7th April 2017) - Pazzaglia, Ugo E.; Congiu, Terenzio; Sibilia, Valeria; Casati, Lavinia; Minini, Andrea; Benetti, Anna
Abstract: A histological and morphometric analysis of human metacarpal and carpal anlagen between the 16th and 22nd embryonic weeks was carried out with the aim of studying the establishment of the respective anlage architecture. No differences in the pattern of growth were documented between the peripheral and central zones of the metacarpal epiphyses and those of the carpals. The regulation of longitudinal growth in long bone anlagen occurred in the transition zone between the epiphysis and the diaphysis (homologous to the metaphyseal growth plate cartilage in more advanced developmental stage of the bone). Comparative zonal analysis was conducted to assess the chondrocyte density, the mean chondrocyte lacunar area, the paired chondrocyte polarity in the orthogonal longitudinal and transverse planes, and the lacunar shape transformation in the metacarpal. In transition from epiphysis to diaphysis chondrocyte density decreased and mean lacunar area increased. No significant differences in the chondrocyte maturation cycle were observed between proximal/distal metacarpal epiphyses and the carpal anlagen. The number of paired chondrocyte oriented along the growth vector was significantly higher in both proximal/distal transition zones between epiphysis and diaphysis. Human metacarpals shared with experimental models (like mice and nonmammal tetrapods) an early common chondrocyte maturation cycle but with a different timing due to the slower embryonic and fetal developmental rate of human anlagen. Abstract : General scheme of the cartilage anlage shape modulation during early growth: a level‐headed, eccentrical chondrocyte proliferation led to the globular shape of short bone anlage (a), while a prevailing, axial proliferation to the elongated shape of long bone anlage (b). Assessment of morphometric parameters and intralacunar, paired chondrocytes was used in the paper to give evidence of intralacunar polarization during fetal development before metaphyseal growth plate frame organization.